Bersih desa traditions in javanese life: cultural studies (case study in Petungrejo village, Nguntoronadi, Magetan regency, East Java) - Malawi, I; Chasanatun, F; Sudjoko, A K H (IOP conference series. Earth and environmental science, 2021)
This study aims was to describe and analyze the implementation of Bersih Desa traditions including the reason for its implementations that was conducted in Petungrejo Village, Nguntoronadi District, Magetan, East Java. This research used a qualitative case study approach by grounded methods that is a study based on empirical field data through observation, interviews with informants who are appropriate to this research study. The subjects were a community that was determined by purposive sampling technique. The data have been taken from primary and secondary sources, and data collection techniques by observation, interviews, and documents. The main instrument in this research was the researcher himself. Based on the results above included analysis and discussion of the research findings, it was found: a) Bersih Desa traditions was an ancestral tradition that is carried out every Suro month on Friday Legi; b) In Bersih Desa ceremony, the symbols are used as an interaction between humans and their environment; c) Some people still have animism and dynamism as a legacy from their ancestors; d) These spiritual values became mental triggers among the community to hold Bersih Desa activities; e) The Bersih Desa traditions were being a syncretism between Islamic teachings and animism dynamism; f) The Bersih Desa traditions contained the social correlation and mutual assistance as a manifestation of noble character; g) The community realizes that the use of mutual cooperation spirit as a form of harmony and cooperation that could be carried out all common interests as well as.